2020
DOI: 10.1039/d0fo00288g
|View full text |Cite
|
Sign up to set email alerts
|

Human-like collagen promotes the healing of acetic acid-induced gastric ulcers in rats by regulating NOS and growth factors

Abstract: Human-like collagen promotes the healing of acetic acid-induced gastric ulcers in rats: possible mechanisms, promotes the expression of growth factors, regulates NOS activity, promotes collagen deposition, and reduces inflammatory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…matsutake peptides on gastric injury might be induced by promoting the expression of certain growth factors and inducing tissue reconstruction. In addition, angiogenesis is essential for wound healing, and VEGF accelerates gastric mucosal recovery by stimulating the rebuilding of the mucosal microvascular network and facilitating the delivery of oxygen and nutrients to the site of injury. , Our research confirmed a decrease in VEGF protein expression in gastric tissues after ethanol stimulation, which is consistent with previous research . Our results also suggested that supplementation with SDLKHFPF and SDIKHFPF could upregulate the expression of VEGF protein.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…matsutake peptides on gastric injury might be induced by promoting the expression of certain growth factors and inducing tissue reconstruction. In addition, angiogenesis is essential for wound healing, and VEGF accelerates gastric mucosal recovery by stimulating the rebuilding of the mucosal microvascular network and facilitating the delivery of oxygen and nutrients to the site of injury. , Our research confirmed a decrease in VEGF protein expression in gastric tissues after ethanol stimulation, which is consistent with previous research . Our results also suggested that supplementation with SDLKHFPF and SDIKHFPF could upregulate the expression of VEGF protein.…”
Section: Discussionsupporting
confidence: 91%
“…29,30 Our research confirmed a decrease in VEGF protein expression in gastric tissues after ethanol stimulation, which is consistent with previous research. 31 Our results also suggested that supplementation with SDLKHFPF and SDIKHFPF could upregulate the expression of VEGF protein. Thus, we deduced that T. matsutake peptides might ameliorate ethanol-induced gastric injury by promoting the expression of angiogenic factors.…”
Section: ■ Discussionsupporting
confidence: 59%
“…The specimens were fixed in 10% neutral formalin then prepared for paraffin blocks. The blocks were cut into 5-mm sections and stained with hematoxylin and eosin for examining the histological structure 19 , periodic acid-Schiff (PAS) for evaluating mucosal glycoprotein production variations in the mucosa of the stomach 20 , and Masson’s Trichrome for detecting collagen fiber deposition 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Type I collagen (Col I), which promotes cellular proliferation, migration, and differentiation, is the support structure of the skin. [ 37 ] Figure 9 a,b shows that among the diabetic chronic wounds in the different groups, the wounds in the ES therapy‐PHTB(TA‐siRNA) hydrogel groups have the highest levels of Col I, which indicates that the combination therapy promotes collagen production. Significant amounts of Col I are detected in fibroblasts, which were labeled with vimentin.…”
Section: Resultsmentioning
confidence: 99%